The effect of Health Literacy on adherence to Diabetes Mellitus Management in patients in Puskesmas - Dwight Mahaputera Marulitua Hutapea; Kimberley Maharani Maulibulung Hutapea (Oshada, 2024)
This study aims to analyze the relationship between health literacy and compliance management of diabetes mellitus in patients at Puskesmas Koni, Jambi. High health literacy is expected to improve patients ' understanding of the importance of diabetes management, which in turn can improve adherence to medication, diet, exercise, and routine controls. This study uses a cross-sectional analytical survey design with 170 respondents selected through purposive sampling. Data were collected using questionnaires that measured levels of health literacy and diabetes management compliance. The results of the analysis showed a significant relationship between the level of health literacy with diabetes management compliance, where patients with better health literacy tend to be more compliant with the treatment and management of their diabetes. These findings suggest that improving health literacy could be an effective strategy to improve patient compliance in diabetes management in health centers.